Spatial remodeling through systematic geological mapping of the Itambé stock of the Estrela do Sul Granitic Suite, Southern Brasília Belt - Ferraz, Douglas Correa [UNESP]; de Araujo, Larissa Marques Barbosa; Petronzio, Juliana Abreu Crosara; Godoy, Antônio Misson [UNESP]; Luna, Crislayne Aparecida (Universidade Federal do Rio Grande do Norte - UFRN, 2024)
The Itambé Granite is one of the seven stocks belonging to the Estrela do Sul Granite Suite in Minas Gerais, occurring near the city of the same name. This Neoproterozoic magmatism is intruded into the metasedimentary sequence of the Araxá Group in the southern portion of the Brasília Belt. This study arose from the urgent need to update the geological maps of the area, as a preliminary analysis, which included satellite image processing, existing maps, and photointerpretation, revealed inconsistencies related to the regional geological map. These inconsistencies are justified by the broad scale of the map, presenting dimensions, extensions, and shapes different from those observed in a detailed scale. It was possible to update the dimensions and extents of the Itambé Granite by using remote sensing and geoprocessing techniques, utilizing Sentinel-2A multispectral satellite images and a digital elevation model, combined with systematic geological mapping, thereby updating the information on the Itambé Granite. The process resulted in the spatial redefinition of the granitic stock, now delineated by an approximate area of 6.2 km², aiming for a better understanding of local and regional geology.
Remodelamento espacial por mapeamento geológico sistemático do stock Itambé da Suíte Granítica Estrela do Sul, porção Meridional da Faixa Brasília
Keywords: Estrela do Sul Granite Suite; Southern Brasília Belt; Stock Itambé